The Portrayal of Women in the Periodicals of the First Lithuanian Republic - Bankauskaitė-Sereikienė, Gabija (Respectus Philologicus, 2012)
This article aims to add to the study of the culture, advertising history, and conception of woman of the first Republic of Lithuania. It examines articles and advertisements for women published from 1920–1940 in the periodicals “Naujoji romuva”, “Moteris” and “Naujas žodis.” The image of woman demanded by the traditional society was in large part formed by the Lithuanian Catholic women’s society through the newspaper “Moteris.” The patriarchal society wanted women to appear modest, healthy, and naturally beautiful, cherishing folk traditions and the image of the village girl with blonde braids. The image of woman-as-sacrificial-hero was also popular. Connotations of femininity were applied to the good, moral mother, the unconditionally loving wife, the guardian of the home, the saviour of the nation, the tutor and teacher who follows the word of God. However, the desire to also see women as active, determined, educated people who were able to hold jobs and take care of themselves demonstrates the broad outlook of the female Catholics. The image of the free-willed Lithuanian woman, as dictated by Western culture, appeared in “Naujoji romuva” and “Naujas žodis.” At its core it emphasised the cult of the body, fashion, external beauty, and personal and sexual freedom. The modern woman was always young, active, dominant in her relationships with men, and took an active interest in cultural events. Emancipated women were not necessarily married, and could raise children without husbands just as well. Yet femininity and faithfulness were valued. The study of the sources shows that women’s individuality, self-identity and need to be active were most likely to be expressed in the social, cultural and artistic spheres. These provided women not only with the opportunity to be educated and emancipated, but also with a place for self-expression, a chance to open their inner world, to form a well-rounded world-view. It is likely that the interwar Lithuanian woman – a middle-class city dweller – was in search of harmony and freedom: to be a bit of a temptress, to be beautiful, to create a happy family, and to make these differing social feminine roles work with her own economic and spiritual emancipation.